Translation and validation of the Neurological Assessment in Neuro-Oncology scale to Brazilian Portuguese - Velho, Maíra Cristina; Andrade Gripp, Daniel; Pires de Aguiar, Paulo Henrique; Nicacio, Joab Alves; Formentin, Cleiton; Greggianin, Gabriel Frizon; Campos, Ana Carolina Pinheiro; Maldaun, Marcos Vinicius Calfat (Frontiers in Neurology, 2024)
Introduction The Neurological Assessment for Neuro-Oncology (NANO) scale was elaborated to assess neurologic function in integration with radiological criteria to evaluate neuro-oncological patients in clinical setting and enable the standardization of neurological assessment in clinical trials. The objective of this study is the translation to Brazilian Portuguese and transcultural adaptation of NANO scale in patients with the diagnosis of glioblastoma, brain metastasis and low-grade glioma. Methods Patients with diagnosis of glioblastoma, brain metastasis, and low-grade glioma were prospectively evaluated between July 2019 and July 2021. The process of translating and cross-culturally adapting the NANO scale included: translation from English to Portuguese, synthesis and initial revision by an expert committee, back-translation from Portuguese to English, a second revision by the expert committee, and the application of the NANO scale. Regarding the reliability of the NANO scale, Cronbach’s alpha was employed to measure the internal consistency of all scale items and assess the impact of item deletion. Additionally, Spearman’s correlation test was used to evaluate the convergent validity between the NANO scale and Karnofsky Performance Scale (KPS). Results One hundred and seventy-four patients were evaluated. A statistically significant inverse relation (p < 0.001) between KPS and NANO scale was founded. The Cronbach’s alpha values founded for NANO scale were 0.803 for glioblastoma, 0.643 for brain metastasis, and 0.482 for low grade glioma. Discussion The NANO scale Brazilian Portuguese version proves to be reproducible and valid to evaluate neuro-oncological patients with glioblastoma and brain metastasis, presenting a strong correlation with KPS scale. Further studies are warranted to assess the validity and reliability of the scale in patients diagnosed with low-grade glioma.